(untitled) (Texas Journal of Medical Science, 2026)
The most common complications associated with cirrhosis are neurological and neuropsychiatric disorders, referred to as hepatic encephalopathy (HE). Proton pump inhibitors (PPI) cannot be without risk, as recent studies have shown a clear link between PPI and conditions such as encephalopathy. IPP work by suppressing acid, which can disrupt intestinal microbiomes. Patients with cirrhosis are at risk of developing hepatic encephalopathy (HE), mainly due to the ammonia produced by the typical intestinal flora, and may subsequently be at risk of changes in this condition if the microbiome changes in any way.